BIOACCUMULATION OF HEAVY METALS IN FRESHWATER SNAILS BELLAMYA BENGALENSIS, AND LYMNEA ACCUMINATA FROM MALANGAON WETLAND OF DHULE DISTRICT (MAHARASHTRA) INDIA - BHALCHANDRA, WAYKAR; RAM, PETARE (The Bioscan, 2013)
The levels of heavy metals zinc, copper, cadmium and lead were determined in surface water, soil sediments and whole soft body tissues of native freshwater snail species, Bellamya bengalensis, and Lymnea accuminata from Malangaon dam. The result showed that in surface water the cadmium (0.0259mg/L) and lead (0.0730 mg/L) concentration exceed higher limit of WHO drinking water standard (WHO, 1993). It was observed that, concentration of four metals zinc (1565.6µg/g), copper (1371.3µg/g), cadmium (90.16µg/g) and lead (125.3µg/g) were higher in soil sediments as compare to surface water. The bioaccumulation levels of zinc, copper, cadmium, and lead in Bellamya bengalensis were 3498.6, 4655.3, 83.5 and 1541.3µg/g respectively and for Lymnea accuminata were 1798.8, 690.1, 107.63 and 603.3.5µg/g respectively. The metal concentrations in whole soft body tissues of snail’s species were higher than the surface water and soil sediments. The metal concentration, BWAF and BSAF values suggested that the Bellamya bengalensis have greater capacity for zinc, copper and lead accumulation than Lymnea accuminata, while Lymnea accuminata has greater capacity for cadmium accumulation than Bellamya bengalensis.